Bibliometric and Visual Analysis on Metabolomics in Coronary Artery Disease Research - Yu, Ning; Wang, Ruirui; Liu, Baocheng; Zhang, Lei (Frontiers in Cardiovascular Medicine, 2022)
Background: Metabolomics has important research value in coronary artery disease, which has drawn an increasing amount of attention over the past decades. Many articles have been published in this field, though no relevant scientometric study has been published yet. Objective: We aim to study metabolomics and coronary artery disease research qualitatively and quantitatively, and visually analyze the development status, trend, and research hotspots of this field, and provide a reference for the research direction in coronary artery disease. Methods: The articles were acquired from the Web of Science Core Collection. VOSviewer and citeSpace software was used to analyze publication growth, country/institution, journal distribution, author, reference, and keyword, and detected the keywords with strong citation bursts to identify the emerging topics. Results: A total of 1121 references were obtained, and the annual number of publications increased over the investigated period. Metabolomics research has presented a gradual upward trend in coronary artery disease during the past 16 years. The USA and China ranked at the top in terms of the percentage of articles. The institution with the highest number of research publications in this field was Harvard University, followed by the University of California System and Brigham Women's Hospital. The most frequently cited authors, including Hazen SL, Tang WH, and Wang ZN. Ala-Korpela M is the most productive author, followed by Clish CB and Adamski, J. The journal with the most publications in this field was Scientific Reports, followed by PLOS One and Journal of Proteome Research. The keywords used at high frequency were "risk", "biomarkers", "insulin resistance", and "atherosclerosis". Burst detection analysis of top keywords showed that "microbiota", "tryptophan", and "diabetes" are the current research frontier in this field. Conclusions: This work has provided some useful information for acquiring knowledge on metabolomics and cardiovascular diseases. Metabolomics research has presented a gradual upward trend in the coronary artery disease study during the past 16 years. The research on the tryptophan metabolism regulated by intestinal flora will become an emerging academic trend in this field, which can offer some guidance for more extensive and in-depth studies in the future.